COVID-19 and socio-materially bounded experimentation in food practices: insights from seven countries. Issue 1 (9th December 2022) - Hoolohan, Claire; Wertheim-Heck, Sigrid C. O.; Devaux, Fanny; Domaneschi, Lorenzo; Dubuisson-Quellier, Sophie; Schäfer, Martina; Wethal, Ulrikke B.
Abstract: COVID-19 has caused unprecedented disruption to previously settled everyday routines, prompting a period of forced experimentation as people have adjusted to rapid changes in their private and working lives. For discussions regarding consumption, this period of experimentation has been interesting, as the apparent instability has disturbed the ongoing trajectory of consumption practices, and with it has created possibilities for a transition toward sustainability. In this article, we examine food practices (e.g., food shopping, preparation, and eating) in seven countries (France, Germany, Italy, Netherlands, Norway, UK, and Vietnam) to assess what we can learn to accelerate transitions toward sustainable consumption. Grounded in a practice theoretical approach, our empirical analysis shows how disruption of everyday routines has generated socio-materially bounded experimentation. We demonstrate commonalities across contexts in how lockdown measures have restricted the performance of previously taken-for-granted practices. We also show diversity in experimentation as food consumption is entangled in other everyday practices. Our study, on one hand, portrays how the adaptation of food practices allows disruption to be managed, demonstrating creativity in working within and around restrictions to continue to provide services for everyday life. On the other hand, we reveal that the capacity of experimentation is not evenly distributed among people and this variation helps in identifying the wider socio-material conditions that constrain and enable opportunities for readjustment. Understanding disparities that affect experimentation (e.g., integration of food practices with work and caring practices) is informative when thinking about how to stimulate sustainability transformations in food practices and provides critical reflections on strategies to enable sustainable consumption.